Two-loop renormalization of a chiral SU(2) gauge theory in dimensional regularization with non-anticommuting γ 5 - Paul Kühler; Dominik Stöckinger (Journal of High Energy Physics)
Abstract Higher order calculations in chiral gauge theories such as the Electroweak Standard Model require a sound treatment of the notoriously problematic γ 5-matrix in Dimensional Regularization (DReg). In the all-order consistent BMHV scheme anticommutativity has to be sacrificed, resulting in spurious breakings of BRST invariance, the restoration of which necessitates finite, symmetry-restoring counterterms. Following recent advances in successfully applying this scheme to multi-loop calculations for Abelian models, we shall here present the first complete non-Abelian two-loop result for the case of SU(2), which is of particular interest to the Standard Model. We provide the complete list of finite, two-loop symmetry-restoring counterterms and discuss intricacies of the non-Abelian implementation. Except for one novel term, the finite counterterm action exhibits the same structure as at one-loop order.